Factors that affect Maybank’s lending in Malacca area from 2003 to 2008 / Muhammad Syahir Saleh - Saleh, Muhammad Syahir (Faculty of Business and Management, 2010)
Maybank is the established bank in Malaysia. Beside that, Maybank Group has over 450 offices in 14 countries namely Malaysia, Singapore, Philippines and etc. With the main products include commercial banking, investment banking and many more. Lending is considered by the banking industry as the most important function for the utilization of funds. Therefore, factors that affect Maybank’s lending in Malacca area should highlighted to ensure them excellence. According to the overall result, this study indicates that the most independent variables give an impact to the Maybank lending is customer deposit. It shows a positive relationship between the both variables. While gross domestic product that measure a negative and significant relationship.